Structural and mechanistic elucidation of inflammasome signaling by cryo-EM. (October 2019) - Shen, Chen; Sharif, Humayun; Xia, Shiyu; Wu, Hao
Highlights: Helical assembly of PYD and CARD is revealed as one universal mechanism for inflammasome signaling by cryo-EM. Cryo-EM facilitates the understanding of disk-like, self-propagating assembly of the NLRC4 inflammasome. The cryo-EM structure of a gasdermin (GSDM) pore uncovers the molecular details of membrane insertion, providing a novel mechanism for cytokine secretion and pyroptosis execution. Abstract : The innate immune system forms an evolutionarily ancient line of defense against invading pathogens and endogenous danger signals. Within certain cells of innate immunity, including epithelial cells and macrophages, intricate molecular machineries named inflammasomes sense a wide array of stimuli to mount inflammatory responses. Dysregulation in inflammasome signaling leads to a wide range of immune disorders such as gout, Crohn's disease, and sepsis. Recent technological advances in cryo-electron microscopy (cryo-EM) have enabled the structural determination of several key signaling molecules in inflammasome pathways, from which macromolecular assembly emerges as a common mechanistic theme. Through the assembly of helical filaments, symmetric disks, and transmembrane pores, inflammasome pathways employ highly dynamic yet ordered processes to relay and amplify signals. These unprecedentedly detailed views of inflammasome signaling not only revolutionize our understanding of inflammation, but also pave the way for the development of therapeutics against inflammatory diseases.